Law Protection on Patients Toward The Health Services Conducted by Social Security Administrator for Health (SSAH) or BPJS in Accordance With The Limitation on Cataract Surgery - Chori Diah Astuti; Suherman Suherman; Arrisman Arrisman (Universitas Katolik Soegijapranata Semarang, 2020)
Health is a primary right of every individual and must be guaranteed by the state; therefore, the state has regulated the health of its citizens as stipulated in the 1945 Constitution Article 28 Section 3 which is further regulated in law No. 40 Year 2004 concerning the national social security system. One of the concerns of the government is that many Indonesians who have reached the age of 50-60 years who experience vision problems due to cloudy eye lense or cataract. The government concern is can be seen from their attention on health problems by passing Minister of Health Regulation No. 29 Year 2016. Concerning with eye Health Care Services at the Health Care Amanities and the Director of Health Service Security on Health (SSAH) passed a regulationNo. 2 Year 2018 concering with cataract service security service.The Method Used in this study is a normative juridical method, using secondary data consisting of primary, secondary and tertiary legal materials. The end purpose of this study is to get clarity about the legal protection of patients against health services by the Health amenities and SSAH or BPJS with the existence of restrictions on cataract surgery and to find out the claim procedures concerning with this restriction.